Mono- and multinuclear PGM complexes containing thiosemicarbazones synthesis, characterization and antiplasmodial evaluation - Adams, Muneebah (Department of Chemistry, 2015)
Four aryl- and ferrocenyl-derived thiosemicarbazone ligands have been synthesized and characterized using NMR, infrared (IR) spectroscopy and mass spectrometry. These ligands were used towards the synthesis of three series of mono- and multinuclear complexes, in which the thiosemicarbazone ligands chelate in either a bidentate (N,S) or tridentate (C,N,S) mode.